Makna Dilahirkan Kembali Bagi Orang Percaya Masa Kini - Suhadi Suhadi; Andreas Sese Sunarko (Jurnal Teologi Berita Hidup, 2021)
Being born again or being born again is one of the important teachings (doctrines) of Christianity. Being born again or being born again is the most radical effect of God's work on the sinner's response to accepting God's redemptive work through Jesus Christ. The new birth is something that must be experienced by every person because it has a tremendous impact on his life, namely someone who is born again or is born again has the potential to see and enter the kingdom of God, become a new creation and gain the status of a child of God. But there are people who don't understand this. Through this paper the writer wants to describe using qualitative methods with a literature study approach. So it can be concluded that the contribution of being born again or the experience of being born again or being born again is important and must be experienced by believers because it has an impact on the eternal value of seeing and entering the kingdom of God. Kelahiran baru atau dilahirkan kembali merupakan salah satu pengajaran (doktrin) yang penting dalam kekristenan. Kelahiran baru atau dilahirkan kembali merupakan dampak pekerjaan Allah yang paling radikal atas respons orang berdosa dalam menerima karya penebusan Allah melalui Yesus Kristus. Kelahiran baru merupakan hal yang harus dialami oleh setiap orang karena membawa dampak yang luar biasa dalam hidupnya yaitu seseorang yang dilahirkan baru atau dilahirkan kembali mendapatkan potensi untuk melihat dan masuk dalam kerajaan Allah, menjadi ciptaan baru dan mendapatkan status sebagai anak Allah. Namun ada orang-orang yang belum memahami hal ini. Melalui tulisan ini penulis ingin mendeskripsikan dengan menggunakan metode kualitatif dengan pendekatan studi literatur. Sehingga dapat disimpulkan bahwa kontribusi kelahiran baru atau pengalaman dilahirkan kembali merupakan hal penting dan harus dialami oleh orang percaya karena berdampak pada nilai kekekalan yaitu melihat dan masuk dalam kerajaan Allah.